The science, technology and innovation policy review: Jamaica (New York, 1999)
The book presents the result of an intensive, year-long exercise which is intended to advance the national dialogue on the importance of innovation and technological change in Jamaica's development strategy. Its recommandation are addressed to the entire innovation community in Colombia
Keywords: development countries - economic conditions - case studies,finance - development countries - case studies,jamaica - economic aspects,jamaica - economic conditions